Effect of Free Cash Flow and Inventory Turnover on Performance of Listed Manufacturing Firms in Nigeria: The Moderating Role of Leverage - Olufemi, Gina Oghogho (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The impact of free cash flow efficiency, inventory turnover, and financial leverage on firm performance remains fragmented and inconclusive in the existing literature, with limited context-specific insights tailored to the Nigerian manufacturing sector. This study examined the effect of free cash flow efficiency, inventory turnover, and financial leverage on the performance of listed manufacturing firms in Nigeria using panel data of 49 companies covering the period 2012 to 2023. Firm performance was proxied by Tobin’s Q, while regression analysis was conducted using the robust random-effects model. This study adopts an ex post facto research design. The findings revealed that financial leverage had a positive and statistically significant effect on firm performance proxied by Tobin’s Q, while free cash flow efficiency and inventory turnover have an insignificant effect on Tobin’s Q. However, the interaction between Free Cash Flow Efficiency and Financial Leverage was positive and significant, suggesting that Financial Leverage moderates the relationship and enhances the effect of Free Cash Flow Efficiency on firm performance. The study concluded that financial leverage, when prudently managed, plays a strategic role in enhancing Tobin's Q, particularly when paired with efficient internal cash flow utilization. Based on these findings, it is recommended that manufacturing firms in Nigeria adopt prudent leverage strategies that complement efficient free cash flow management, as the combined effect significantly enhances market valuation and overall firm performance.